HOW TO MOTIVATION SUSTAIN BUSINESS STUDENTS? - Alan Adityawijaya; Liliana Dewi (STIE Mahardhika, 2018)
This research aimed to invesitgate the exploration of intrinsic and extrinsic motivation for the sustainability of Ciputra University’s student’ businesses. Using a qualitative approach. This study employed semi-structured interview for a data collection method. The key informants of this present study involved are 3 Student’s businesses wich still continues after 7th semesters, 1 student’s business wich is ended in 7 th semester, 1 Human Resource Managements lecturer who understand human empowerment in doing business, and 1 IBM-Practice coordinator who understand motivation factor In Student business sustainability. This study found there’s 3 extrinsic motivation and 4 intrinsic motivation students need to maintain their business’ sustainability. Qualification is the first intrinsic motivation, because the matriculants recognized, they should be going to Ciputra University for studying business. Need for independence and responsibility were also intrinsic motivation drive student’s business’ sustainability. Self-actulization was the basic of all motivation. The first extrinsic motivation was student’s task completion, so the students’ businesses were run to grade achievement. Resources and group-mate also drive student’s motivation for maintaining their businesses’ sustainability.